Black nanostructured Nb2O5 with improved solar absorption and enhanced photoelectrochemical water splitting1. Issue 22 (14th June 2015) - Cui, Houlei; Zhu, Guilian; Xie, Yian; Zhao, Wei; Yang, Chongyin; Lin, Tianquan; Gu, Hui; Huang, Fuqiang
<x xml:space="preserve">Abstract</x> Oxygen-deficient black Nb2O5 nanochannels are successfully prepared, and studied as efficient photoanodes for photoelectrochemical water splitting for the first time.